A metáfora da filosofia enquanto uma iniciação como chave de leitura do pensamento socrático-platônico - Pinto, Sebastião Lima Holanda (2021)
This work investigates the hypothesis that the recurrent metaphor - present in the context of Socratic-Platonic thought -, which characterizes philosophy as a process analogous to an initiation into the mysteries, can be applied in the articulation of a privileged hermeneutic key that gives an embracing understanding of Socrates and Plato's philosophy. At first, we investigate the difficulty imposed to us, contemporary observers, when trying to understand the nature of philosophical activity - as described by Socrates and Plato - from our contemporary Philosophy paradigm, undertaking, for this, an examination of three structural problems: 1) the criticism concerning the limits of the logos present in Platonic dialogues; 2) the signs of continuity between religious experience - especially those that which concerns the ancient Greek mystery cults - and Socratic-Platonic Philosophy; 3) the indications that Socratic-Platonic Philosophy is not reducible to a mere activity of theoretical disinterested explanation of reality, but that it concerns, above all, a practical activity that is oriented towards the realization of certain specific ends. With that in mind, we investigate the hypothesis that exploring the meaning of the characterization of Philosophy as an initiation rite can give us a privileged understanding paradigm that allows us to integrate those three questions - which emerge as problematic for a reading of them from our contemporary paradigm of Philosophy - in a comprehensive, non-conflicting unit. To do this, we explore the nature of the experience of the mysteries in Ancient Greece, and then we demonstrate the evidences of the appropriation of the ritual structure and the initiatic language, proper to the Eleusinian mysteries, at Plato's Symposium, to then investigate the general meaning of the characterization of philosophy as an initiatory rite in Socratic-Platonic thought, and thus demonstrate how this metaphor helps to clarify the very nature of Socratic-Platonic philosophy.